The Study of food spectrum of Liza abu (Heckel,1843) in the lower part of Al-Asaad Lake Reservoir (Raqqa, Syria) - مجاهد بطل, محمد; منصور , كاترين; ديب, ديم (Latakia University Journal -Biological Sciences Series, 2022)
Liza abu (330) individuals, were collected from The Lower Part of Al-asaad Lake Reservoir, during the period from 25/10/2019 to 25/9/2020. Standard length ranged between 11.5-24 cm, and total weight ranged 35-180 g. Their main food was detritus (32.54, 99.15, 28.12) according to the Points(P), Frequency of Occurrence(O) and Index of Relative Importance (IRI) methods respectively. Secondly phytoplankton (25.13, 95.79, 22.48), respectively. In the Third place Diatoms. Food items included Aquatic planets and their seeds, zooplankton, sand, and other foods materials were also found. It was recorded that the higher feeding amplitude in Winter season ( 22.65 point \ fish ) and the lower feeding amplitude was recorded in Autumn (46.66% point \ fish ). This results indicated that liza abu is a Omnivorous and bottom feeder fish.